Identifikasi Faktor Ketahanan Remaja 10–19 Tahun dari Pernikahan Dini Tahun 2020 - Elvira Naftali Anastasya; Liza Kurnia Sari (Seminar Nasional Official Statistics, 2022)
Applications for marriage dispensation that went to the Supreme Court reached 64.196, which is a far cry from the previous year of 2019. This study aims to analyze what factors increase adolescent resilience by using four factors, namely environmental, educational, socioeconomic, and social media with six independent variables. This study also used secondary data sourced from susenas KOR 2020 conducted by the Central Statistics Agency with survival analysis of the Accelerated Failure Time (AFT) method. The results of the analysis in this study found that all resilience factors, namely environmental factors, educational factors, socioeconomic factors, and social media factors, can increase the resilience of adolescents 10-19 years from early marriage in Indonesia in 2020. The government and the entire community must be more assertive in preventing early marriage in this case the government can emphasize that in all parts of Indonesia, marriages should not occur before the age of 19.